Design of Automatic Recharging System of Robot Based on RFID Radio Frequency Technology - Xiao, Zheng (Recent Advances in Electrical & Electronic Engineering, 2021)
Background: In order to study the interference of wired transmission mode on robot motion, a mobile robot attitude calculation and debugging system based on radio frequency (RF) technology are proposed. Methods: Microcontroller STM32 has been used as the control core for the attitude information of the robot by using MEMS gyroscope and accelerometer. The optimal attitude Angle of the robot is calculated through nRF24L01, which is the core of the wireless communication module, attitude acquisition module and wireless data communication upper computer application platform. Results: The results show that the positioning accuracy is better than ± 5mm. Conclusion: The experimental results show that the proposed attitude solving and debugging system of mobile robot based on RF technology has better reliability and real-time performance. The propped model is convenient for the debugging of the mobile robot system and has certain engineering application value.
Keywords: positioning accuracy